2005
DOI: 10.1203/01.pdr.0000180540.55990.eb
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Zinc Deficiency Influences Arterial Blood Pressure and Vascular Nitric Oxide Pathway in Growing Rats

Abstract: There is an increasing interest in the involvement of trace elements such as zinc in the pathogenesis of cardiovascular diseases. This study was designed to examine whether moderate zinc deficiency during growth influences blood pressure (BP) and vascular nitric oxide (NO) pathway. Three-week-old weaned male Wistar rats were randomly divided into two dietary groups and fed either a moderately zinc-deficient diet (zinc content 9 mg/kg; n ϭ 12) or a control diet (zinc content 30 mg/kg; n ϭ 12) for 60 d. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 36 publications
4
34
0
1
Order By: Relevance
“…As reported previously, rats fed a moderate zinc-deficient diet showed a significant fall in plasmatic, urinary and fecal levels, indicating that the diet was successful to induce a moderate zinc deficiency (Tomat et al, 2005). Moreover, kidney zinc concentration was lower in ZD rats compared with C rats (C = 27.63 ± 1.99 vs. ZD = 22.40 ± 0.77 ⁎ μg/g tissue, ⁎ p b 0.01).…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…As reported previously, rats fed a moderate zinc-deficient diet showed a significant fall in plasmatic, urinary and fecal levels, indicating that the diet was successful to induce a moderate zinc deficiency (Tomat et al, 2005). Moreover, kidney zinc concentration was lower in ZD rats compared with C rats (C = 27.63 ± 1.99 vs. ZD = 22.40 ± 0.77 ⁎ μg/g tissue, ⁎ p b 0.01).…”
Section: Resultssupporting
confidence: 70%
“…We previously showed that ZD diet group exhibited higher levels of systolic blood pressure from day 30 (C: 114 ± 4 vs. ZD: 131 ± 3 mm Hg, p b 0.001) up to the end of dietary treatment compared with the C group (C: 122 ± 3 vs. ZD: 150 ± 3 mm Hg, p b 0.001) (Tomat et al, 2005).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations